HIJAB SEBAGAI SIMBOL KEAGAMAAN: PEMAKNAAN KATA HIJAB MENURUT ULAMA KLASIK DAN KONTEMPORER - Aisyah Nurul Aini; Abdul Aziz (IAT IAIN Pontianak, 2024)
The hijab is still an interesting issue to discuss. Moreover, how classical and contemporary scholars study and interpret it. In this article, we examine the issue of the hijab from two perspectives which are considered quite ontradictory, namely from the perspective of classical ulama and contemporary ulama. The importance of this research is to look critically at the differences in the meaning of the hijab according to classical and contemporary scholars and how they interpret the verse of the Qu’ran which discuss the hijab for women. This article focuses on the opinion of Imam Zamakhsyari as a classical scholar and the opinion of Qasim Amin as a contemporary scholar. This research is a type of library research using qualitative methods and collecting data using documentation techniques from several literatures that are in accordance with the theme raised. From this research it was found that in interpreting the word hijab, Qasim Amin tends to be looser than Imam Zamakhsyari and several other classical scholars.